Single-Cell RNA Sequencing Reveals Cellular and Transcriptional Changes Associated With Traumatic Brain Injury - Xing, Jin; Ren, Li; Xu, Hao; Zhao, Liang; Wang, Zhi-Han; Hu, Guang-Dong; Wei, Zi-Long (Frontiers in Genetics, 2022)
Traumatic brain injury (TBI) is currently a substantial public health problem and one of the leading causes of morbidity and mortality worldwide. However, the cellular and transcriptional changes by TBI at single-cell level have not been well characterized. In this study, we reanalyzed a single-cell RNA sequencing (scRNA-seq) dataset to identify the key cellular and transcriptional changes associated with TBI. Specifically, we found that oligodendrocyte accounted for the highest proportion, and replacement of mature oligodendrocytes by the immature oligodendrocytes might be associated with TBI. Astrocyte was significantly expanded and activated in TBI. The enhanced activity of inflammatory response-related pathways in the astrocyte of TBI samples suggested that the astrocytes, not microglia that are the major resident immune cells of the brain, were responsible for the inflammation in the acute phase of TBI. The hormone transport and secretion and exocytosis were upregulated in the excitatory neurons of TBI gave us a hint that excitatory neurons might excessively transport and excrete glutamate in response to TBI. Moreover, the ependymal subpopulation C0 was significantly enriched in TBI characterized by downregulation of cilium movement, indicating that the attenuated activity of cilium movement by TBI might decrease cerebral spinal fluid flow. Furthermore, we observed that downregulated genes in response to the candesartan treatment were preferentially expressed by excitatory neurons and involved in pathways like neuronal system and neuroactive ligand-receptor interaction, indicating that candesartan might promote the recovery of neurons after traumatic brain injury via reducing the neuroactive ligand-receptor interactions and cellular excitotoxicity. In conclusion, our study identified key cell types involved in or response to TBI, which improved our understanding of the cellular and transcriptional changes after TBI and the molecular mechanism of the therapeutic target.